2019
DOI: 10.1038/s41598-019-38721-5
|View full text |Cite
|
Sign up to set email alerts
|

Compressing the lumbar nerve root changes the frequency-associated cerebral amplitude of fluctuations in patients with low back/leg pain

Abstract: Understanding the central mechanisms responsible for lumbar nerve root compression may facilitate the development of new therapeutic strategies. In this study, our aim was to investigate the amplitude of fluctuations (AF) in five specific frequency bands and the full-frequency band realm to provide novel insight into the rhythm of the neuronal activity of low back/leg pain (LBLP) patients (n = 25). Compared with healthy controls, LBLP patients exhibited a significantly altered AF in multiple brain regions, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
(74 reference statements)
1
5
0
Order By: Relevance
“…Functional connectivity results suggest that, as pain becomes chronic (i.e., >1 y), the NAc subcircuitries fc show dynamic changes. We therefore studied power spectral density (PSD) (20, 21) because this approach uncovered meaningful differences among clinical populations (22) including chronic pain patients (23)(24)(25)(26)(27)(28)(29). We calculated PSD for different frequency bands defined in previous neurophysiological and fMRI studies (21,30,31) in bilateral NAc and compared among groups using a hypothesis-based approach.…”
Section: Sbpp and Sbpr Show Differences In Corticostriatal Functionalmentioning
confidence: 99%
“…Functional connectivity results suggest that, as pain becomes chronic (i.e., >1 y), the NAc subcircuitries fc show dynamic changes. We therefore studied power spectral density (PSD) (20, 21) because this approach uncovered meaningful differences among clinical populations (22) including chronic pain patients (23)(24)(25)(26)(27)(28)(29). We calculated PSD for different frequency bands defined in previous neurophysiological and fMRI studies (21,30,31) in bilateral NAc and compared among groups using a hypothesis-based approach.…”
Section: Sbpp and Sbpr Show Differences In Corticostriatal Functionalmentioning
confidence: 99%
“…Physiological signals in the same brain network might compete or cooperate with each other in different frequency bands 36 . Our previous study showed that LBLP patients exhibit pain-related alterations in the cerebral amplitude of fluctuations and that regional homogeneity was frequency-dependent in several brain regions 5 , 18 . Thus, our study further proves that specific frequency ranges should be selected for the detection of pain-related intrinsic activity in LBLP patients.…”
Section: Discussionmentioning
confidence: 97%
“…BOLD signal fluctuations in different frequency bands may demonstrate different neurophysiological mechanisms 15 . Studies on fMRI generally consider the typical frequency band (0.01–0.1 Hz) to be of physiological significance 16 , 17 , but some studies of pain have found that the high frequency band (> 0.167 Hz) may also convey meaningful information 4 , 5 , 18 21 . Thus, the aim of this study was to determine whether the experience of persistent pain and paresthesia (numbness) influence the frequency-related cross- and within-network sFC and temporal variability in the dynamic pain connectome in LBLP patients.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with low back and leg pain, researchers have found a significant increase in ALFF in regions such as the inferior parietal lobule and medial prefrontal cortex ( Zhou et al, 2018 ; Zhou et al, 2019 ). Besides, the insula, amygdala, hippocampal/parahippocampal gyrus, and thalamus have been also found sensitive to pain intensity changes ( Zhang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%